Alexithymia mediates the association between childhood trauma and adolescent E-cigarette use. (1st July 2022) - Sutherland, Benjelene D.; Fallah-Sohy, Nilofar; Kopera, Maciej; Jakubczyk, Andrzej; Sutherland, Matthew T.; Trucco, Elisa M.
Abstract: Background: Adolescent electronic cigarette use (e-cigarette) is a public health concern and factors associated with vaping remain to be understood. Childhood emotional abuse/neglect is a risk factor for e-cigarettes. Yet, pathways by which trauma impacts use remain unclear. Alexithymia (i.e., difficulties identifying and describing feelings) is one possible link. Indeed, emotional abuse/neglect leads to difficulties identifying and verbalizing emotions. This impairment may lead to distress and promote e-cigarette use as a coping strategy. Methods: Using parallel mediation, this study examined the degree to which alexithymia, assessed using the Toronto Alexithymia Scale, mediates the link between emotional abuse/neglect, assessed using the Child and Adolescent Trauma Screen, and e-cigarette use. The sample ( n = 166) consisted of adolescents from a larger multi-wave study. Results: Emotional abuse/neglect predicted difficulty describing feelings (effect = 0.23, p = 0.001), which in turn predicted e-cigarette use (effect = 0.30, p = 0.004). Moreover, difficulty describing feelings mediated the link between emotional abuse/neglect and e-cigarette use (sum of indirect 95% CI [1.68, 16.48]). Difficulty identifying feelings was not a significant mediator and the externally-oriented thinking subscale was excluded due to low reliability. Conclusions: As e-cigarettes are often used in social contexts, teens who experience difficulty describing feelings may vape as a means of connecting emotionally with others. Moreover, nicotine, found in most e-cigarettes, releases dopamine and noradrenaline in the brain modulating action, learning, and memory processes; plausibly, improving verbalization of emotions. Programming which identifies nuances in alexithymia among adolescents with emotional abuse/neglect could mitigate e-cigarette use or delay initiation. Highlights: The link between childhood trauma and e-cigarette use via alexithymia was tested. Emotional abuse/neglect predicted alexithymia among adolescents. Difficulty describing (not identifying) feelings predicted e-cigarette use. Emotional abuse/neglect was not directly associated with e-cigarette use. Treatment linked with emotion verbalization could mitigate e-cigarette use onset.